The use of snake venom derived fibrin glue in hysterorrhaphy of ovine caesarean surgery - Chalhoub, M. [UNESP]; Prestes, N. C. [UNESP]; Lopes, M. D. [UNESP]; Rocha, N. S. [UNESP]; Thomazini-santos, I. A. [UNESP]; Mendes-giannini, M.j. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2000)
Fibrin glue has been used on its own or in conjunction with suturing materials to promote hemostasis, reduce adherence, strengthen the wound site, and improve healing. Snake venom derived fibrin glue was evaluated as an alternative to conventional uterine suturing after ovine caesarean surgery. Twenty-eight pregnant ewes of known mating date were used. The animals submitted to conventional caesarean sections showed a better wound healing process. As expected, all the operated animals had retained placenta, compromising coaptation of wound edges. This had a strong influence in the results observed with the animals in which fibrin glue was used. The animals were divided into four groups GI, GII, GIII, and GIV and sacrificed, respectively, 3, 7, 15, and 30 days after surgery for macro and microscopic examination of the uterus. From each group, six animals underwent surgery using fibrin glue and four animals were submitted to comparative conventional hysterorrhaphy using catgut.
Keywords: Fibrin tissue adhesive; viper venoms; uterus; sheep; fibrin glue